The Effect Of The Prophet Ayub Bibliotherapy On Self-Concept Of Chronic Renal Failure Patients Undergoing Hemodialysis - Muhammad Sowwam; S. Sudaryanto; Muhammad Erfaâ€™I (Gaster, 2022)
Â Chronic renal failure is a clinical condition characterized by an irreversible decline in renal function requiring hemodialysis therapy or kidney transplantation. Routine hemodialysis therapy for CRF patients is at risk of negatively affecting self-concept. Bibliotherapy of the Prophet Ayub story to increase the patient's understanding of himself, broaden his cultural horizons, and provide various emotional experiences is expected to increase a more positive self-concept. Purpose: This study aimed to determine the effect of bibliotherapy of the Prophet Ayub story on the self-concept of chronic kidney failure patients undergoing hemodialysis at PKU Muhammadiyah Hospital, Sragen. Methods: This study is quasi-experimental (Quasi-experimental) with a pre-test and post-test design. The subjects of this study were 46 patients with chronic kidney disease who underwent hemodialysis at PKU Muhammadiyah Sragen Hospital. Data analysis used Paired T-test with a confidence level of 95%. Results: Bibliotherapy of the Prophet Ayub story influenced the self-concept of chronic kidney failure patients undergoing hemodialysis at PKU Muhammadiyah Hospital, Sragen. Conclusion: There is a positive effect of bibliotherapy of the Prophet Ayub story on the self-concept of chronic kidney failure patients undergoing hemodialysis.